SURVEY ON THE CONSUMPTION OF WINE IN SICILY - Maurizio, Lanfranchi; Carlo, Giannetto (Strategii Manageriale, 2012)
The survey on consumption of wine has been conducted in the period between April 20th and July 10th of 2011 on a sample of 200 consumers of Sicily. The recognition by the administration of the product was mainly conducted at some outlets, supermarkets, wine shops and bars, interviewing a sample of consumers directly with the method "face to face." The survey purpose was conducted to understand the needs of wine consumers and the role played by the mark of quality in the choice of purchase, and finally the degree of appreciation and consumption of Sicilian wine.